Role of Cyclin-Dependent Kinase 1 in Translational Regulation in the M-Phase - Kalous, Jaroslav; Jansová, Denisa; Šušor, Andrej (Cells, 2020)
Cyclin dependent kinase 1 (CDK1) has been primarily identified as a key cell cycle regulator in both mitosis and meiosis. Recently, an extramitotic function of CDK1 emerged when evidence was found that CDK1 is involved in many cellular events that are essential for cell proliferation and survival. In this review we summarize the involvement of CDK1 in the initiation and elongation steps of protein synthesis in the cell. During its activation, CDK1 influences the initiation of protein synthesis, promotes the activity of specific translational initiation factors and affects the functioning of a subset of elongation factors. Our review provides insights into gene expression regulation during the transcriptionally silent M-phase and describes quantitative and qualitative translational changes based on the extramitotic role of the cell cycle master regulator CDK1 to optimize temporal synthesis of proteins to sustain the division-related processes: mitosis and cytokinesis.
Keywords: M-phase; Animals; TOR Serine-Threonine Kinases; Cell Cycle; lidé; 4E-BP1; messenger RNA; buněčný cyklus; RNA, Messenger; CDK1; Cell Cycle Proteins; translation; proteinkinasa CDC2; CDC2 Protein Kinase; mRNA; zvířata; TOR serin-threoninkinasy; mTOR; proteiny buněčného cyklu; Humans